1994
DOI: 10.1111/j.1365-2338.1994.tb01063.x
|View full text |Cite
|
Sign up to set email alerts
|

European oak declines and global warming: a theoretical assessment with special reference to the activity of Phytophthora cinnamomi

Abstract: Causes of current severe declines of the deciduous oaks Quercus robur and Q. petraea in northern and central Europe and of the evergreen Q. ilex, Q. suber and other Quercus spp. in the Mediterranean area are reviewed. Factors implicated include drought, pollution, winter cold, flooding, and stress‐related attacks by insects and fungi. Additional factors in Mediterranean oak declines include changing land‐use patterns and root disease caused by the aggressive, exotic oomycete root pathogen Phytophthora cinnamom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 17 publications
6
106
0
4
Order By: Relevance
“…Geralmente, os autores simplificam a metodologia assumindo um valor constante de temperatura ou precipitação a ser somado ou subtraído nos valores médios atuais, independentemente da época do ano e da região geográfica estudada, como por exemplo, Boag et al (1991) para o estudo do efeito das mudanças climáticas em nematóides fitopatogênicos, Xiphinema e Longidorus, na Europa; Luo et al (1995) para simulações com brusone do arroz em países asiáticos; Brasier & Scott (1994) e Brasier (1996 para a ocorrência de Phytophthora cinnamomi Rands em carvalho (Quercus spp.) no continente europeu; fitopatógenos na Finlândia por Carter et al (1996) e no Reino Unido, por Clifford et al (1996).…”
Section: Resultsunclassified
“…Geralmente, os autores simplificam a metodologia assumindo um valor constante de temperatura ou precipitação a ser somado ou subtraído nos valores médios atuais, independentemente da época do ano e da região geográfica estudada, como por exemplo, Boag et al (1991) para o estudo do efeito das mudanças climáticas em nematóides fitopatogênicos, Xiphinema e Longidorus, na Europa; Luo et al (1995) para simulações com brusone do arroz em países asiáticos; Brasier & Scott (1994) e Brasier (1996 para a ocorrência de Phytophthora cinnamomi Rands em carvalho (Quercus spp.) no continente europeu; fitopatógenos na Finlândia por Carter et al (1996) e no Reino Unido, por Clifford et al (1996).…”
Section: Resultsunclassified
“…Changing weather (e.g. temperature, rainfall) can induce severe plant disease epidemics (Coakley et al 1999;Chakraborty 2005), which threaten food security if they affect staple crops (Luo et al 1995;Chakraborty et al 2000;Anderson et al 2004) and can damage landscapes if they affect amenity species (Brasier & Scott 1994;Bergot et al 2004). Severity of human, animal and plant disease epidemics is greatly affected by climatic factors, especially temperature and rainfall (Wint et al 2002;Fitt et al 2006a; Thomson et al 2006;Bosch et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Modelling approaches have included those matching existing climates in one region with climates predicted for another (Brasier & Scott 1994) or combinations of simulation models for crop growth and disease development (Luo et al 1995). Before 1999, no work had used predicted climate variables generated by new more sophisticated general circulation models (GCMs); most studies had relied on predictions of fixed changes in temperature and rainfall (Coakley et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are also in accordance with Marçais et al (1996), who confirmed the effect of higher winter temperatures and orientation in the most heated side of the stem girth in P. cinnamomi survival in stems of red oak. In accordance with the modelling of P. cinnamomi behaviour as a result of climate change (Brasier, Scott 1994;Marçais et al 1996;Brasier 1996;Bergot et al 2004), we expect that warming will significantly enhance the impact of PAA in its locations.…”
Section: Discussionmentioning
confidence: 71%
“…Recent models predict an increase in the distribution and local impact of a range of forest pathogens, including P. cinnamomi (Desprez-Loustau et al 2007). Winter survival is a dominant cue for the development of ink disease caused by this pathogen in oak in Europe (Brasier, Scott 1994;Marçais et al 1996;Bergot et al 2004). Therefore, we predict that winter temperatures will play a key role in the survival of other invasive Phytophthora spp.…”
mentioning
confidence: 99%